Analisis Graph Clustering Terhadap User Behaviour di Official Account Pagaralam_Insta - Bagas Hijra Primantara; Ilman Zuhri Yadi (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The popularity of social media in recent years since it was first discovered in the late 1990s has continued to grow, especially Facebook and Instagram which became popular in 2010. This is because social media connects hundreds of millions of people around the world without understanding geographic boundaries. Instagram social media is a group of applications based on the internet and web.2.0 technology that allows the exchange and creation of user-generated content. This study examines the Pagaralam_Insta media account which focuses on information media in the fencealam and surrounding areas and analyzes how Instagram users interact with the content uploaded by the Pagaralam_Insta account (User Behavior Analytic). The results showed that the level of posts that users were interested in was News and Promotions. In news, there is interest from users, it can be seen that the number of nodes and edges formed is long, as well as the topic of Promotional news.